Quality of life and mood of patients and family caregivers during hospitalization for hematopoietic stem cell transplantation. Issue 6 (2nd December 2014) - El‐Jawahri, Areej R.; Traeger, Lara N.; Kuzmuk, Kailyn; Eusebio, Justin R.; Vandusen, Harry B.; Shin, Jennifer A.; Keenan, Tanya; Gallagher, Emily R.; Greer, Joseph A.; Pirl, William F.; Jackson, Vicki A.; Ballen, Karen K.; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND We conducted a study to investigate the impact of hospitalization for hematopoietic stem cell transplantation (HCT) on the quality of life (QOL) and mood of patients and family caregivers (FC). METHODS We conducted a longitudinal study of patients who were hospitalized for HCT and their FC. We assessed QOL (using the Functional Assessment of Cancer Therapy‐Bone Marrow Transplantation) and mood (using the Hospital Anxiety and Depression Scale) at baseline (6 days before HCT), day +1, and day +8 of HCT. We administered the Medical Outcomes Study Health Survey Short Form‐36 to examine FC QOL (Physical Component Scale and Mental Component Scale). To identify predictors of changes in QOL, we used multivariable linear mixed models. RESULTS We enrolled 97% of eligible patients undergoing autologous (30 patients), myeloablative (30 patients), or reduced intensity (30 patients) allogeneic HCT. Patients' QOL markedly declined (mean Functional Assessment of Cancer Therapy‐Bone Marrow Transplantation score, 109.6 to 96.0; P<.0001) throughout hospitalization. The percentage of patients with depression (Hospital Anxiety and Depression Scale‐Depression score of >7) more than doubled from baseline to day +8 (15.6% to 37.8%; P<.0001), whereas the percentage of patients with anxiety remained stable (22.2%; P = .8). These results remained consistent when data were stratified by HCT type. Baseline depression (β, −2.24; F, 42.2 [P<.0001]) and anxiety (β, −0.63; F, 4.4 [P =.03]) were found to independently predict worse QOL throughout hospitalization. FC QOL declined during the patient's hospitalization (physical component scale: 83.1 to 79.6 [P =.03] and mental component scale: 71.6 to 67.4 [P =.04]). CONCLUSIONS Patients undergoing HCT reported a steep deterioration in QOL and substantially worsening depression during hospitalization. Baseline anxiety and depression predicted worse QOL during hospitalization, underscoring the importance of assessing pre‐HCT psychiatric morbidity. Cancer 2015;121:951–959. © 2014 American Cancer Society.